Mixed Adenoneuroendocrine Carcinoma of the Colon Progressed Rapidly After Hepatic Rupture: Report of a Case - Ito, Hiromitsu (The International College of Surgeons, World Federation of General Surgeons and Surgical Specialists, Inc., 2014)
The rupture of a metastatic mixed adenoneuroendocrine carcinoma (MANEC) has not been previously reported, although the neuroendocrine cell carcinoma is often associated with a high incidence of hepatic metastases. The patient was a 39-year-old male who presented with upper abdominal pain over 3 months. Computed tomography showed multiple tumors in both hepatic lobes, while lower gastrointestinal endoscopy revealed a tumor in the transverse colon. Histopathologic examination of the tumor revealed it to be a neuroendocrine cell carcinoma. After the resection of the primary tumor, hepatic metastases rapidly increased, and one of them in the left lateral segment was ruptured with significant hemorrhage. The rupture led us to undertake the emergency operation to stop the bleeding. Histology showed a high-grade large-cell neuroendocrine carcinoma associated with moderately differentiated tubular adenocarcinoma. The Ki-67 labeling index was 80% (G3). The diagnosis was mixed adenoneuroendocrine carcinoma according to the 2010 World Health Organization guidelines. Hepatic arterial infusion chemotherapy, systemic chemotherapy, and transcatheter arterial chemoembolization did not decrease the tumor progress, and the patient died on postoperative day 110. Reporting this highly malignant case, I hope all doctors can be interested in MANEC.